Thermodynamic and theoretical-based modeling and assessment of an energy-efficient performance measurement system in the soldering process - Esfandyari, Alireza; Kreitlein, Sven; Schmidt, Elias; Franke, Jörg (2016 Electronics Goes Green 2016+, EGG 2016, 2017)
This paper presents methods for the assessment and evaluation of two energy efficiency strategies for the soldering process in the field of electronics production. The first method evaluates the electrical energy consumption performance through the energy value modeling in the production process level. In the second method, also other energy resources rather the electrical energy consumption is considered. This method assesses the quality of resource conversion in the soldering process in the product level. In this paper, firstly, the system of the least energy demand as crossbench reference value is explained. The basic idea of this calculation is the comparison and evaluation of electrical energy efficiency based on the ratio of the theoretically required energy consumption to the measured electrical energy consumption. In the second method, the model quantifies the resource consumption and qualifies this consumption using the exergy analysis method. Exergy efficiency is the fraction of the work potential of the heat that is converted to work, and it illustrates the quality of consumed resources during the soldering process. Transparency and comparison of these two methods derives the measures to analyze and improve the major energy saving potentials in the soldering oven technology.
CRIS-Team Scopus Importer:2023-03-07